Impact of coexistent chronic obstructive pulmonary disease on the survival of patients with small cell lung cancer receiving chemotherapy. Issue 10 (14th August 2018) - Ju, Sunmi; Lee, Hyang Rae; Kim, Ju‐Young; Kim, Ho Cheol; Lee, Gyeong‐Won; You, Jung Wan; Cho, Yu Ji; Jeong, Yi Yeong; Lee, Jong Deog; Lee, Seung Jun
Abstract : Background: While there is growing interest in the correlation between chronic obstructive pulmonary disease (COPD) and non‐small cell lung cancer, very few studies have examined the interaction between COPD and small cell lung cancer (SCLC). Therefore, the aim of this study was to examine the impact of COPD on the survival of patients with SCLC. Methods: The medical records of 110 patients with SCLC who received chemotherapy from July 2006 until April 2014 were retrospectively examined. The overall survival (OS) and progression‐free survival (PFS) rates of spirometry‐diagnosed COPD and non‐COPD groups were compared. Predictors for poorer survival were analyzed using Cox proportional hazards regression. Results: Of the 110 SCLC patients, 57 (51.8%) had coexistent COPD. The median OS for the COPD group was 11.6 months and for the non‐COPD group was 11.2 months (log‐rank test, P = 0.581), whereas the median PFS rates were 6.65 and 6.57 months, respectively (log‐rank test, P = 0.559). Multivariate analysis identified Eastern Cooperative Oncology Group performance status ≥ 2 and extensive‐stage SCLC as independent risk factors for shorter OS; however, coexisting COPD was not a predictor of survival. Conclusions: Although over half of the SCLC patients receiving chemotherapy had COPD, coexisting COPD had no impact on the survival of patients with SCLC.